Norma kompetencyjna art. 384 k.c. do określania szczególnych warunków umów konsumenckich - Radwański, Zbigniew (Wydział Prawa i Administracji UAM, 1996)
The author believes in rejecting the concept of regulating consumer contracts through directives of the Council of Ministers issued on the grounds of a general competence norm, which had been adopted under the Polish People's Republic. It follows from the overall premisses of the civil law which functions in a market economy that the fundamental tool for shaping the contents of civil and legal relations should be a contract together with general conditions of contracts universally applied in mass consumer turnover. It is not the state but the parties - or one of them upon the permission of the other - which are to decide upon the contents of the relations in question, with implementation of dispositive norms excluded. The state's role ought to consist, above all, in controlling the general conditions of the contracts and not in their issuing. This is the direction indicated by the directive of the EEC 93/13, of April 5th 1993, under which the member countries are obliged to define in their legislation unlawful clauses in contracts with consumers.
Competence norm, Art. 384 of the Civil Code, for defining particular conditions for consumer contracts